2D MXene: A Potential Candidate for Photovoltaic Cells? A Critical Review - Muhammad Ahsan Saeed (18418575) (2022)
The 2D transition metal carbides/nitrides (2D MXenes) are a versatile class of 2D materials for photovoltaic (PV) systems. The numerous advantages of MXenes, including their excellent metallic conductivity, high optical transmittance, solution processability, tunable work‐function, and hydrophilicity, make them suitable for deployment in PV technology. This comprehensive review focuses on the synthesis methodologies and properties of MXenes and MXene‐based materials for PV systems. Titanium carbide MXene (Ti3C2Tx), a well‐known member of the MXene family, has been studied in many PV applications. Herein, the effectiveness of Ti3C2Tx as an additive in different types of PV cells, and the synergetic impact of Ti3C2Tx as an interfacial material on the photovoltaic performance of PV cells, are systematically examined. Subsequently, the utilization of Ti3C2Tx as a transparent conductive electrode, and its influence on the stability of the PV cells, are discussed. This review also considers problems that emerged from previous studies, and provides guidelines for the further exploration of Ti3C2Tx and other members of the 2D MXene family in PV technology. This timely study is expected to provide comprehensive understanding of the current status of MXenes, and to set the direction for the future development in 2D material design and processing for PVs. Other Information Published in: Advanced Science License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/advs.202104743